Exploring student engagement with peer feedback on L2 writing - Fan, Yumei; Xu, Jinfen (Journal of second language writing, 2020)
•The study examined EFL students’ multidimensional engagement with different forms of peer feedback.•They had positive affective engagement and extensive behavioral and cognitive engagement with the form-focused feedback.•They showed a tendency of low cognitive and behavioral engagement with the content-focused feedback.•The findings revealed a complex relationship within the sub-constructs of and among the three engagement dimensions. While the past few decades have witnessed enormous growth in research on peer feedback in second and foreign language (L2) writing, little attention has been paid to student engagement with peer feedback. Drawing on multiple methodologies, we explored how 21 university EFL students engaged with peer feedback on L2 writing affectively, behaviorally, and cognitively. We collected multiple sources of data, including audio-recorded peer feedback sessions, students’ composition drafts, written peer feedback, semi-structured interviews, and a questionnaire survey. Findings showed that student engagement with peer feedback differed depending on the type of feedback. Overall, students had positive affective engagement and extensive behavioral and cognitive engagement with the form-focused feedback but showed a tendency of low cognitive and behavioral engagement with the content-focused feedback. Additionally, the study revealed a complex relationship within the sub-constructs of and among the three engagement dimensions, manifested in the form of interconnectedness and inconsistencies. We discuss pedagogical implications about how to enhance student engagement with peer feedback.